A Bulk Retrospective Study of Robot-Assisted Stereotactic Biopsies of Intracranial Lesions Guided by Videometric Tracker - Liu, Huan-Guang; Liu, Yu-Ye; Zhang, Hua; Meng, Fan-Gang; Zhang, Kai; Zhu, Guan-Yu; Chen, Ying-Chuan; Liu, De-Feng; Zhang, Jian-Guo; Yang, An-Chao (Frontiers in Neurology, 2021)
Background: Biopsies play an important role in the diagnosis of intracranial lesions, and robot-assisted procedures are increasingly common in neurosurgery centers. This research investigates the diagnoses, complications, and technology yield of 700 robotic frameless intracranial stereotactic biopsies conducted with the Remebot system. Method: This research considered 700 robotic biopsies performed between 2016 and 2020 by surgeons from the Department of Functional Neurosurgery in Beijing's Tiantan Hospital. The data collected included histological diagnoses, postoperative complications, operation times, and the accuracy of robotic manipulation. Results: Among the 700 surgeries, the positive rate of the biopsies was 98.2%. The most common histological diagnoses were gliomas, which accounted for 62.7% of cases (439/700), followed by lymphoma and germinoma, which accounted for 18.7% (131/700) and 7.6% (53/700). Bleeding was found in 14 patients (2%) by post-operation computed tomography scans. A total of 29 (4.14%) patients had clinical impairments after the operation, and 9 (1.29%) experienced epilepsy during the operation. The post-biopsy mortality rate was 0.43%. Operation time—from marking the cranial point to suturing the skin—was 16.78 ± 3.31 min (range 12–26 min). The target error was 1.13 ± 0.30 mm, and the entry point error was 0.99 ± 0.24 mm. Conclusion: A robot-assisted frameless intracranial stereotactic biopsy guided by a videometric tracker is an efficient, safe, and accurate method for biopsies.